Therapeutic potential of natural coumarins in autoimmune diseases with underlying mechanisms - Li, Yan; Wang, Guan-qing; Li, Yan-bin (Frontiers in Immunology, 2024)
Autoimmune diseases encompass a wide range of disorders characterized by disturbed immunoregulation leading to the development of specific autoantibodies, which cause inflammation and multiple organ involvement. However, its pathogenesis remains unelucidated. Furthermore, the cumulative medical and economic burden of autoimmune diseases is on the rise, making these diseases a ubiquitous global phenomenon that is predicted to further increase in the coming decades. Coumarins, a class of aromatic natural products with benzene and alpha-pyrone as their basic structures, has good therapeutic effects on autoimmune diseases. In this review, we systematically highlighted the latest evidence on coumarins and autoimmune diseases data from clinical and animal studies. Coumarin acts on immune cells and cytokines and plays a role in the treatment of autoimmune diseases by regulating NF-κB, Keap1/Nrf2, MAPKs, JAK/STAT, Wnt/β-catenin, PI3K/AKT, Notch and TGF-β/Smad signaling pathways. This systematic review will provide insight into the interaction of coumarin and autoimmune diseases, and will lay a groundwork for the development of new drugs for autoimmune diseases.